2012
DOI: 10.1021/cg300416x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Clathrate Hydrate Growth in Gas/Liquid/Liquid System

Abstract: Variation in crystal growth behavior of clathrate hydrate depending on the temperature and pressure was visually demonstrated in the krypton-gas/liquid-cyclopentane/ liquid-water system, which is expected to be a working medium of highly efficient hydrate-based heat pumps. The experiments were conducted at 28 different temperature− pressure conditions in the range from 279.0 to 299.7 K and from 0.59 to 6.44 MPa. It was found that the behavior of the hydrate crystal growth in this three-component system can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Δ T sub is the difference between the experimental temperature T ex of crystal formation and the phase equilibrium temperature T eq of hydrates (Δ T sub ≡ T eq - T ex ). In the previous studies, the relationships between Δ T sub and the crystal growth of sI and sII hydrates were revealed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Δ T sub is the difference between the experimental temperature T ex of crystal formation and the phase equilibrium temperature T eq of hydrates (Δ T sub ≡ T eq - T ex ). In the previous studies, the relationships between Δ T sub and the crystal growth of sI and sII hydrates were revealed.…”
Section: Introductionmentioning
confidence: 98%
“…They also reported that the crystal morphology of hydrates grown in liquid water changed from polygonal or triangular flat plates to dendritic with increasing Δ T sub . Ishida et al. , observed the crystal growth of the sII hydrate formed on a water droplet partially immersed in liquid cyclopentane and exposed to HFC-32 (difluoromethane) and krypton gases. They classified the crystal growth dynamics into three modes which were called “cover”, “expansion”, and “line” depending on the conditions of temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CP hydrate formation have been observed in previous studied by Sakemoto et al, 17 Ishida et al, 18 Karanjkar et al, 19 Mitarai et al, 20 and recently Marti ́nez de Banõs et al 21 All previous investigations indicate a growth in two stages: (i) nucleation at the interface and (ii) growth depending upon the temperature, the presence of a surfactant, or properties of the wall surfaces. Our objective is to study a single water drop 22,23 as a simplified model of an emulsion of water in CP with an oilsoluble surfactant, sorbitan monooleate (Span 80), test the results of Karanjkar et al, 14,19 and add new data to understand the complex morphogenesis of this relatively simple system.…”
Section: ■ Introductionmentioning
confidence: 84%
“…Since the CP mass fraction in ideal CP hydrates was 0.186, a large amount of excessive free CP molecules would be found in the system as the CP mass fraction reached 0.25 and 0.3 as seen in Table 2. Based on previous analysis, the mixed CP-CO 2 hydrate tended to form at the interphase between CP and brine at the initial stage so that excessive CP molecules were not beneficial to the hydrate growth [40,41]. In addition, excessive CP molecules could increase the thickness of liquid CP film on aqueous brine and hydrate particles, which increased the diffusion resistance of CO 2 molecules.…”
Section: Effect Of the Cp Mass Fractionmentioning
confidence: 98%